2012
DOI: 10.1002/ijc.27655
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of signal transducer and activator of transcription 3 in soft tissue leiomyosarcoma is associated with a better prognosis

Abstract: Signal transducer and activator of transcription (STAT) 3 mediates a broad range of biological processes, including cell survival and proliferation, and STAT3 has generally been regarded as a pro-oncogenic transcription factor. We investigated the phosphorylation status of STAT3 and the protein expression of the suppressor of cytokine signaling 3 (SOCS3) by immunohistochemistry in 145 formalin-fixed, paraffin-embedded samples of soft tissue leiomyosarcoma (LMS), including 129 primary tumors. Eight benign soft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
1
19
1
Order By: Relevance
“…Intriguingly, it has also been reported that high nuclear expression of Tyr705-phosphorylated STAT3 is correlated with improved survival, smaller tumors, or less aggressive histology in various tumors, including breast cancer [73,74], head and neck cancer [75], lung cancer [76], gastric cancer [77], soft tissue leiomyosarcoma [78], and advanced rectal cancer [79]. However, in pancreatic ductal adenocarcinoma, no association was seen between STAT3 phosphorylation and patient survival [80].…”
Section: Jak/stat Signaling In Different Cancer Typesmentioning
confidence: 99%
“…Intriguingly, it has also been reported that high nuclear expression of Tyr705-phosphorylated STAT3 is correlated with improved survival, smaller tumors, or less aggressive histology in various tumors, including breast cancer [73,74], head and neck cancer [75], lung cancer [76], gastric cancer [77], soft tissue leiomyosarcoma [78], and advanced rectal cancer [79]. However, in pancreatic ductal adenocarcinoma, no association was seen between STAT3 phosphorylation and patient survival [80].…”
Section: Jak/stat Signaling In Different Cancer Typesmentioning
confidence: 99%
“…Grabner et al [33] detected STAT3 may act as a tumor suppressor through STAT3-NF-κB-IL-8 axis in KRAS mutant lung adenocarcinoma and a molecular marker with favorable prognostic value. In the same line of evidence, it was shown that p-STAT3 was reported as a favorable prognosis marker in breast cancer [15], head and neck squamous cell carcinoma [16], and leiomyosarcoma [34]. Amongst the STAT family, STAT3 is the most studied STAT in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of SOCS3 causes the development of cancer cells in the human lung [24] . On the other hand, SOCS3 overexpression suppresses the apoptosis pathway in prostate cancer and is associated with decreased survival in leiomyosarcoma [5,25] . The function of SOCS3 in neoplasms thus remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…STAT proteins are then phosphorylated, and they translocate to the nucleus and exert transcriptional control. Although sev-eral studies have linked STAT3 to tumor growth and metastases in various types of neoplasms [3,4] , it was reported that STAT3 activation is also correlated with a better prognosis in some tumors [5,6] . STAT3 seems to have a double-sided effect on tumor progression.…”
Section: Phosphorylation Of Stat3 Inmentioning
confidence: 99%
See 1 more Smart Citation